Analisis Pola Konsumsi Ibu Rumah Tangga Terhadap Jajanan Pasar Tradisional Berbahan Baku Umbi-Umbian - Cornelia Alessandra (BiSTeK Pertanian, 2021)
Tuber crops are plants containing 20% carbohydrates which are the result of plant sources of carbohydrates in addition to grains and corn. Types of these tubers include cassava, sweet potato, taro, ganyong, erut, kimpal, and others. In Indonesia which plays an important role of tubers are cassava or cassava and sweet potato (Dahlia, 2006). Factors influencing the demand of snack market based on tubers in Malang City consist of several factors, namely the age of housewife, education, number of household member, price of snack market of tubers, price of other goods, gethuk lindri price, household. The result of this research are (1) Age influence to buying snack market equal to -0,094 (2) Education housewife 0,307 (3) Number of household member 0,628 (4) Price of mud cakes -0,208 (5) Price gethuk lindri - 0,316 (6) Household income -0.424.